Uncanny bodies the coming of sound film and the origins of the horror genre - Spadoni, Robert (University of California Press, 2007)
In 1931 Universal Pictures released Dracula and Frankenstein, two films that inaugurated the horror genre in Hollywood cinema. These films appeared directly on the heels of Hollywood's transition to sound film. Uncanny Bodies argues that the coming of sound inspired more in these massively influential horror movies than screams, creaking doors, and howling wolves. A close examination of the historical reception of films of the transition period reveals that sound films could seem to their earliest viewers unreal and ghostly. By comparing this audience impression to the first sound horror films, Robert Spadoni makes a case for understanding film viewing as a force that can powerfully shape both the minutest aspects of individual films and the broadest sweep of film production trends, and for seeing aftereffects of the temporary weirdness of sound film deeply etched in the basic character of one of our most enduring film genres.
Keywords: Horror films : United States : History and criticism; Sound motion pictures : History and criticism; 20th century american culture; 20th century american film history; american culture; american film history; american movie history; audience reception; cinema; classic horror cinema; dark; dracula; early sound film; film studies; filmmaking; frankenstein; hollywood cinema; horror genre; horror movies; intense; modality; movie studies; sound film; svengali; the hollywood review of 1929; uncanny theater; united states of america; universal pictures; vampires; ventriloquism